2021
DOI: 10.1136/bcr-2021-244853
|View full text |Cite
|
Sign up to set email alerts
|

High-titre convalescent plasma therapy for an immunocompromised patient with systemic lupus erythematosus with protracted SARS-CoV-2 infection

Abstract: A 39-year-old woman with systemic lupus erythematosus treated with anti-CD20 monoclonal antibody rituximab was admitted to our hospital with COVID-19 pneumonia. Despite receiving dexamethasone, she developed hypoxaemia and persistent lung opacities. As bronchoalveolar lavage was suggestive of cryptogenic organising pneumonia, high-dose corticosteroid was administered, and she received antimicrobial therapy for opportunistic infections without improvement. Reverse transcription PCR was repeatedly positive for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…For these exploratory analyses, 13 uncontrolled large case series without individual patient data enrolling 358 participants were included in descriptive analysis . In this study, 125 case reports or case series enrolling 265 participants were included for patient-level exploratory analyses. One study was included in both the descriptive analysis and the individual patient data analysis because individual patient data were available only for a subgroup of patients.…”
Section: Resultsmentioning
confidence: 99%
“…For these exploratory analyses, 13 uncontrolled large case series without individual patient data enrolling 358 participants were included in descriptive analysis . In this study, 125 case reports or case series enrolling 265 participants were included for patient-level exploratory analyses. One study was included in both the descriptive analysis and the individual patient data analysis because individual patient data were available only for a subgroup of patients.…”
Section: Resultsmentioning
confidence: 99%
“…As described in the "Direct Acting Antivirals" section, Brown et al suggested that combination of RDV and passive humoral therapy is superior to RDV alone for clearing protracted infections [41•]; however, Hueso et al used CCP alone with success [46•]. Smaller case series and case reports have shown clinical improvement and/or viral clearance [48][49][50][51][52][53], while others have failed to show effectiveness [2,6].…”
Section: Convalescent Plasmamentioning
confidence: 99%
“…In some patients, polymerase chain reaction (PCR) tests for SARS-CoV-2 can yield positive results for approximately 80–300 days from the initial positivity [ 5 6 7 ]. Prolonged SARS-CoV-2 infection poses a public health threat as it may lead to a higher number of viral mutations, potentially resulting in the emergence of drug-resistant variants and variants with increased infectivity [ 8 9 ].…”
Section: Introductionmentioning
confidence: 99%